CORRELATION BETWEEN IMMUNOLOGICAL INDEXES OF THE ORAL LIQUID IN CHILDREN WITH CHRONIC CATARRHAL GINGIVITIS - Malko, N.V.; Hasiuk, P.A.; Ivanchyshyn, V.V.; Vorobets, A.B.; Kalashnikov, D.V.; Zubchenko, S.G. (World of Medicine and Biology, 2019)
Human pathology arising from changes in ecological homeostasis is considered as an ecological pathology, and according to the literature, about 8-9% of all diseases can be considered as eco-caused, moreover, in economically developed countries this figure is significantly higher. In order to assess the adaptive capabilities of the children's organism and to determine the risk factors for the development of a periodontal tissue lesion the immunological parameters of the oral liquid were studied, correlation analysis between the indices of oral liquid immunological status in children, their age and place of residence was carried out. Results of the performed study show that in children of both groups suffering from chronic catarrhal gingivitis the concentration of immunoglobulins decreases with age increase, the number of leukocytes and the level of pro-inflammatory cytokines significantly grows, while the level of anti-inflammatory cytokines decreases, but thеse processes were more pronounced in children from ecologically unfavorable regions.
Keywords: children; gingivitis; oral liquid; immunoglobulins; cytokines; leukocytes; ecological situation